Implementing an early-life nutrition intervention through primary healthcare: staff perspectives - Natalie Garzon Osorio; Frøydis Nordgård Vik; Christine Helle; Elisabet Rudjord Hillesund; Nina Cecilie Øverby; Sissel H. Helland; Penelope Love; Mary Elizabeth Barker; Wim van Daele; Marianne Hope Abel; Harry Rutter; Tormod Bjørkkjær; et al. (BMC, 2024)
Abstract Background Nutrition interventions targeting early childhood can be cost-effective and may provide lifelong, intergenerational benefits. From October 2022 to April 2023 the Nutrition Now (NN) e-learning resource was implemented within Early Childhood Education and Care centres and the Maternal and Child Healthcare Centre (MCHC) in a southern Norwegian municipality. As part of the NN project, the present study aims to explore the MCHC staff's experiences with implementing the NN resource, to gain insights into measures important to scale up digital early-life nutrition interventions. Methods Three group interviews were conducted among public health nurses and midwives alongside one individual interview with the department leader of a MCHC in May 2023. An inductive thematic analysis, as described by Braun and Clarke, was conducted to generate the key themes and subthemes regarding the implementation process of NN within the MCHC. Results Three main themes were generated: [1] Important resource but not always utilized; [2] Parents are interested but had issues with access; and [3] Staff and stakeholder buy-in and commitment needed from the start. Overall, the staff viewed the NN resource as a potential tool for promoting diet-related topics and believed it could support the guidance they were already providing parents. However, few staff members fully familiarized themselves with the resource. While staff perceived parents as positive when informed about NN, they believed issues such as access challenges, competing platforms, and time constraints reduced parental engagement. Lastly, staff suggested improvements for NN's implementation, including enhanced training, better planning, assigning champions, and lowering the threshold for access. Conclusion The findings of this study suggest that the real-world implementation of digital evidence-based health behaviour interventions is feasible but would be enhanced by employing strategies focusing on engagement and utilization. Trial registration The main study is registered in the ISRCTN registry with ID ISRCTN10694967, https://doi.org/10.1186/ISRCTN10694967 . (Registration date: 19-06-2022).